ExoMol line lists – XXIX. Therotation-vibration spectrum of methyl chloride up to 1200 K. Issue 3 (11th June 2018) - Owens, A; Yachmenev, A; Thiel, W; Fateev, A; Tennyson, J; Yurchenko, S N
ABSTRACT: Comprehensive rotation-vibration line lists are presented for the two main isotopologues of methyl chloride, 12 CH3 35 Cl and 12 CH3 37 Cl. The line lists, OYT-35 and OYT-37, are suitable for temperatures up to T=1200 K and consider transitions with rotational excitation up to J = 85 in the wavenumber range 0 – 6400 cm −1 (wavelengths λ 1.56 μ m). Over 166 billion transitions among 10.2 million energy levels have been calculated variationally for each line list using a new empirically refined potential energy surface, determined by refining to 739 experimentally derived energy levels up to J = 5, and an established ab initio dipole moment surface. The OYT line lists show excellent agreement with newly measured high-temperature infrared absorption cross-sections, reproducing both strong and weak intensity features across the spectrum. The line lists are available from the ExoMol database and the cds database.